2014
DOI: 10.1186/preaccept-1004172062141452
|View full text |Cite
|
Sign up to set email alerts
|

SLC29A1 single nucleotide polymorphisms as independent prognostic predictors for survival of patients with acute myeloid leukemia: an in vitro study

Abstract: Background: The mechanism behind poor survival of acute myeloid leukemia (AML) patients with 1-barabinofuranosylcytosine (Ara-C) based treatment remains unclear. This study aimed to assess the pharmacogenomic effects of Ara-C metabolic pathway in patients with AML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
(43 reference statements)
1
5
0
Order By: Relevance
“…In addition, single nucleotide polymorphisms (SNPs) for nucleoside transporters exist that correlate both with toxicity and therapeutic efficacy of dF-dC in pancreatic cancer [ 82 ]. Similar roles of expression levels as well as polymorphisms have been reported for ara-C in the treatment of AML [ 83 , 84 , 85 , 86 , 87 ]. More recently, alternative transport mechanisms for ara-C and dF-dC, involving the SLC22 family, have been described, correlating with overall survival of AML patients treated with ara-C [ 282 ].…”
Section: Tumour-specific Resistance To Nucleobase/nucleoside Analosupporting
confidence: 71%
“…In addition, single nucleotide polymorphisms (SNPs) for nucleoside transporters exist that correlate both with toxicity and therapeutic efficacy of dF-dC in pancreatic cancer [ 82 ]. Similar roles of expression levels as well as polymorphisms have been reported for ara-C in the treatment of AML [ 83 , 84 , 85 , 86 , 87 ]. More recently, alternative transport mechanisms for ara-C and dF-dC, involving the SLC22 family, have been described, correlating with overall survival of AML patients treated with ara-C [ 282 ].…”
Section: Tumour-specific Resistance To Nucleobase/nucleoside Analosupporting
confidence: 71%
“…Many studies also reported that functional abnormalities in SLC29A1were associated with AML resistance to Ara-C [ 25 , 26 ]. In previous studies, SLC29A1 genetic variants (such as rs693955, rs9394992, and rs324148) were associated with treatment outcomes in AML patients [ 27 , 28 ]. In terms of rs3734703, only two studies reported that AML patients with a high frequency of the major “C” allele (in other words, low MAF) of rs3734703 had a poor response to Ara-C-based therapy [ 29 ], while another study [ 30 ] did not find any rs3734703 associations with CR or RFS after induction chemotherapy with AML.…”
Section: Discussionmentioning
confidence: 99%
“…It is the most common form of acute leukemia in adults and the second most common form of leukemia in children after acute lymphoblastic leukemia (ALL) [ 1 , 2 ]. Pediatric AML comprises up to 20% of all childhood leukemia and the mechanism behind poor survival of acute myeloid leukemia (AML) patients remains unclear [ 3 ]. Several novel recurrent mutations have been found to involve epigenetically regulated genes in AML, including DNMT3A [ 4 , 5 ], TET2 [ 6 , 7 ], and IDH1/2 [ 8 ], which are involved in the regulation of DNA methylation, and EZH2 [ 9 , 10 ] and ASXL-1 [ 11 ], which are implicated in the regulation of histones [ 11 ].…”
Section: Introductionmentioning
confidence: 99%